2022
DOI: 10.1055/a-1937-1155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Serum BMP-4, BMP-2, GDF-15, MMP-9, GP39 Levels in Pregnant Women with Obesity and the Related Comorbidities Diabetes Mellitus and Gestational Hypertension

Abstract: Aims We evaluated the clinical value of selected serum biomarkers BMP-4, BMP-2, GDF-15, MMP-9, and GP39 in pregnant women with obesity and the comorbidities diabetes mellitus (DM) and gestational hypertension (GHT). Methods This observational study had groups of controls, including healthy pregnant women; women with only obesity, including pregnant women with BMI≥30 kg/m2; women with gestational DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several studies supported a positive correlation between GDF-15 levels and pulmonary artery pressure, which can be employed to predict pulmonary hypertension [ [50] , [51] , [52] ]. Elevated serum GDF-15 have also been observed in obese women with gestational hypertension [ 53 ]. GDF-15 is a well-recognized inflammatory and stress factor whose expression is increased by pressure overload and sympathetic nervous system activation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies supported a positive correlation between GDF-15 levels and pulmonary artery pressure, which can be employed to predict pulmonary hypertension [ [50] , [51] , [52] ]. Elevated serum GDF-15 have also been observed in obese women with gestational hypertension [ 53 ]. GDF-15 is a well-recognized inflammatory and stress factor whose expression is increased by pressure overload and sympathetic nervous system activation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most women with GDM are overweight or obese, with the clinical features of metabolic syndrome (31). Yarsilikal Guleroglu et al (32) reported that FPG and HbA1c levels in women with GDM and obesity were higher than those in normal pregnant women. The present study found that the incidence of obesity in the GDM group was significantly higher than that in the normal pregnancy group and the mean BMI was also significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al (40) reported that serum GDF-15 levels were independently correlated with cardiovascular risk scores in patients with new-onset T2DM. Yarsilikal Guleroglu et al (32) found that the serum GDF-15 level was higher in GDM patients with obesity than in healthy pregnant women, indicating that GDF-15 is not only associated with gestational hypertension but may also be associated with obesity. Banerjee et al (20) showed that GDF-15 had a significant positive correlation with fasting serum insulin, HOMA-IR and FPG at 24-28 weeks of gestation in subjects with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…CCR2 [461], FASLG (Fas ligand) [462], CD28 [463], LYZ (lysozyme) [464], CCL5 [465], CCL3 [466], C6 [467], MSR1 [468], HGF (hepatocyte growth factor) [469], VEGFA (vascular endothelial growth factor A) [470], ADM (adrenomedullin) [471], CR2 [472], MAG (myelin associated glycoprotein) [473], CDH1 [474], OLIG2 [475], SEMA4D [476], ADAMTS4 [477], BMP2 [478], ERBB3 [479] and NKX2-2 [480] have been identified as a hub gene in spinal cord injury in several studies. CCR2 [481], FASLG (Fas ligand) [286], CD24 [482], CD28 [483], LYZ (lysozyme) [484], IL7R [485], CCL5 [486], LTF (lactotransferrin) [487], GPNMB (glycoprotein nmb) [488], CTLA4 [489], IRF4 [490], CHIT1 [491], NPY2R [492], TAB2 [131], CD52 [302], CD163 [493], MSR1 [306], HGF (hepatocyte growth factor) [494], TRPM8 [495], TTR (transthyretin) [496], F13A1 [497], ADM (adrenomedullin) [498], COL9A3 [499], ANGPTL4 [500], CHI3L1 [501], BMP8A [502], SREBF1 [503], CDKN1C [504], INSIG1 [505], ATF3 [506], HK2 [507], TF (transferrin) [508], MOG (myelin oligodendrocyte glycoprotein) [509], ADAMTS4 [510], BMP2 [511], HSPA2 [512], LMNA (lamin A/C) [330], HSD11B1 [513], NKX2-2 [514], NHLH2 [433], FGF11 [515], ASPA (aspartoacylase) [336], FASN (fatty acid synthase) [516], PNPLA3 [517], MMP15 [518], CBR1 [519], LRP2 [520], WNT7A [340], GPR142 [521], GPD1 [343], LIPE (lipase E, hormone sensitive type) [522], CNDP1 […”
Section: Discussionmentioning
confidence: 99%